471 LET'S TALK DEMENTIA. (14th June 2021) - Ashraf, M; Mahmood, A; Honney, K
Abstract: Introduction: By 2021 over one million people will be living with dementia (1) costing the government an estimated £30bn a year (2). However, cognitive decline is often misdiagnosed or missed completely in hospital admissions, resulting in delays in detection and treatment for patients. Quick and simple screening tools such as the Abbreviated Mental Test Score (AMTS) could help provide early detection and faster treatment times for such patients. Data from Queen Elizabeth Hospital Kings Lynn showed that only 56.8% of patients over the age of 75 were being assessed for cognitive function on admission, while the national targets are set at 90%. Methods: A multi-cycle, trust wide, quality improvement project was used to improve screening outcomes for dementia in QEHKL. A baseline measure of screening was taken by QEHKL coding department. Five PDSA (Plan Do Study Act) cycles were undertaken, implementing interventions to aid screening at each stage. Examples include improved medical clerking booklets, trust wide education and allocated ward 'Dementia Champions'. Performance was assessed by auditors, through patient notes and discharge letters. Results: Over a 4-month period, 432 patient notes were inspected on six medical wards. Results after interventions showed a significant rise in Dementia Screening from 58.7% to 89.8%. AMTS completion was 70.7% in September 2020 on medical wards which improved to 85.7% in November 2020. Results were collected during the COVID-19 pandemic however, COVID wards were excluded. Conclusion: The QI project has highlighted that education and accessible tools can improve cognitive screening numbers. An important note is, due to increased pressures during the COVID pandemic it is plausible that screening rates were adversely affected. Despite this, our figures still show positive improvement. The next cycle of our project includes surgical wards and we expect by the time of presentation to have this data to show.